1966
DOI: 10.2105/ajph.56.11.1874
|View full text |Cite
|
Sign up to set email alerts
|

Alienation as a deterrent to well-child supervision.

Abstract: A study is reported in which two components of alienation, social isolation, and powerlessness, were measured in Negro and white mothers who were medically indigent. The findings are reported and their implications for a more active, "reaching out" type of delivery of well-child services are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…How much do you think about what your health will be like in the future? [1] Not at all [2] Very little [4] Somewhat [5] A great deal 3. How satisfied are you with your ability to count on good health?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…How much do you think about what your health will be like in the future? [1] Not at all [2] Very little [4] Somewhat [5] A great deal 3. How satisfied are you with your ability to count on good health?…”
Section: Methodsmentioning
confidence: 99%
“…How satisfied are you with your ability to count on good health? [1] Extremely satisfied [2] Somewhat satisfied [4] Somewhat dissatisfied [5] Extremely dissatisfied…”
Section: Methodsmentioning
confidence: 99%
“…The total adsorption was raised to 463.7 mg of adsorbates per gram of carbon in 180 minutes. Morris (1966) reported an enhancing effect on total adsorptive capacity by mixed components in both batch and fluidized column studies. The present study further substantiate this phenomenon.…”
Section: Studies a T Thementioning
confidence: 98%
“…A suggestion of the maximum use of the adsorptive capacity of activated carbon is proposed in this report. Morris (1964Morris ( , 1966 reported some enhancement of total adsorptive capacity of carbon in mixed adsorbates solution. For example, the quantity of ABS adsorbed from a pure solution In a mixture of ABS, quinine and 2-sec-butyl-4, 6-dinitophenol (DNOSBP), the quantity of ABS adsorbed [with similar initial concentration) after 100 hours was about 130 micromoles per gram of carbon.…”
Section: Introductionmentioning
confidence: 99%
“…One of the central characteristics of the emotionally mature person is the ability to withstand stress or at least not to be immobilized by it (Dean 1964(Dean , 1966Cole et al 1980). Alienation, on the other hand, has been shown by several studies to be inversely related to the confrontation of one's problems: Richardson (1963) found alienation related to opposition to fluoridation; Morris et al (1966) determined that alienation was a deterrent to well-child supervision; Gray, Kesler and Moodey (1967) found alienation inversely related to immunization; and Hoppe and Heller (1975) found that alienation was negatively related to utilization of health services by Mexican Americans. Seeman et al (1985) found alienation negatively related to health, as did Wethington (1986), and Seeman and Anderson related alienation to alcoholism (1984).…”
Section: Hypothesesmentioning
confidence: 99%